The Absence of Serotonin in the Brain Alters Acute Stress Responsiveness by Interfering With the Genomic Function of the Glucocorticoid Receptors - Sbrini, Giulia; Brivio, Paola; Peeva, Polina Mineva; Todiras, Mihail; Bader, Michael; Alenina, Natalia; Calabrese, Francesca (Frontiers in Cellular Neuroscience, 2020)
psychiatric pathologies, such as depression. We took advantage of tryptophan hydroxylase (TPH) 2 deficient rats, characterized by a complete absence of serotonin in the brain, to evaluate whether a vulnerable genotype may influence the reaction to an acute stressor. In this context, we investigated if the glucocorticoid receptor (GR) genomic pathway activation was altered by the lack of serotonin in the central nervous system. Moreover, we analyzed the transcription pattern of the clock genes that can be affected by acute stressors. Adult wildtype (TPH2+/+) and TPH2-deficient (TPH2-/-) male rats were sacrificed after exposure to one single session of acute restraint stress. Protein and gene expression analyses were conducted in the prefrontal cortex. The acute stress enhanced the translocation of GRs in the nucleus of TPH2+/+ animals. This effect was blunted in TPH2-/- rats, suggesting an impairment of the GR genomic mechanism. This alteration was mirrored in the expression of GR-responsive genes: acute stress led to the up-regulation of GR-target gene expression in TPH2+/+, but not in TPH2-/- animals. Finally, clock genes were differently modulated in the two genotypes after the acute restraint stress. Overall our findings suggest that the absence of serotonin within the brain interferes with the ability of the HPA axis to correctly modulate the response to an acute stress, by altering the nuclear mechanisms of the GR and modulation of clock genes expression.